Strategi Membangun Media Daring Melalui Komunikasi Pemasaran Terpadu (Studi Kasus Pada Bertuahpos.com) - Gunawan Saleh; Prsetia Rahmad (Program Studi Ilmu Komunikasi, 2018)
Advertising is determining whether or not this online mass media develops. For that the online mass media can not only write and disseminate information, but also must be able to communicate in the context of business communication. The method in this research is descriptive qualitative with interview. The results of interviews with four informants, and concluded that Bertuahpos.com doing business communication strategy through socialization conducted social dimedia, it is intended to introduce bertuahpos.com to masyarakat.Untuk establish effective business communication, bertuahpos.com coffe morning with resource persons. In addition, Bertuahpos.com offers advertisements either directly or indirectly through advertising offer proposals, thereby increasing the company's financial objectives through the advertisements it receives. Bertuahpos.com also provides a means for readers to sell products for free on business store content to enhance viewers. Keywords: Strategy, Online Media, Integrated Marketing Communications.